A Self-Report on the Knowledge of Oral Hygiene Among Students of Allied Health in North India - A Cross-Sectional Research - Thorat, Jaywant Shivaji; Thorat , M. M.; Sahoo, Jharashree Kashinath (Journal of Coastal Life Medicine, 2023)
Objective: This cross-sectional study's goal was to assess the oral hygiene knowledge and behaviors that students studying allied health in North India self-reported. Methods: For the study, 500 students from diverse allied health programs were chosen. Data on their understanding, attitudes, and practices on oral hygiene were gathered using a self-administered questionnaire. There were a total of 18 questions in the questionnaire, some of which included demographic information. Descriptive statistics were used to examine the data, and tables were used to show the findings. Results: 500 allied health students from north Indian colleges participated in the study. Knowledge of oral hygiene scored 6.4 out of 10 on average (SD=1.9). An awareness of oral hygiene was high in 35%, moderate in 48%, and low in 17%. The scores for the groups with high, moderate, and low knowledge were 8.5 (SD=0.7), 6.8 (SD=0.6), and 4.1 (SD=0.6), respectively. Knowledge level was strongly impacted by gender and field of study (p=0.001 and p=0.02, respectively). The mean score for nursing students was the highest (7.1), while the mean score for female participants was higher (6.7 vs. 5.8). The average scores for brushing teeth, using dental floss, and cleaning the tongue were, respectively, 6.5 (SD=1.7), 4.8 (SD=2.0), and 4.2 (SD=1.9). The most common knowledge related to tongue cleansing was dental brushing. Conclusion: The study found that although allied health students in North India had a strong understanding of oral hygiene procedures, their actual implementation of such procedures fell short of expectations. Interventions are required to encourage this population to practice improved oral hygiene.